Tectonic evolution of the deepwater Orange Basin (offshore South Africa) using 3D reflection seismic data: implications for hydrocarbon systems - Mahlalela, Vuyolwethu (My University, 2018)
This study applies seismic attributes to the high-resolution 3D reflection seismic data acquired for the deepwater exploration block in the Orange Basin, offshore South Africa, to provide insight into the mechanisms controlling deformation in hydrocarbon systems. The seismic interpretation was carried out on high-resolution, prestack time-migrated 3D seismic data that image post-rift sequences from the Upper Cretaceous to the Quaternary. Three post-rift sequences were identified in the seismic sections; post-rift sequences II, IV and V. Two slumping events caused by gravity failure of the margin were also identified in the Coniacian to Santonian (post-rift sequence II) and Late Cenozoic (post-rift sequence V) sequences. The seismic data also image a thrust fault system in the lower slope, which is interpreted to have been formed by episodic gravity failure from the Coniacian to Santonian. The geometry of this thrust fault system formed independently from the two detachment levels which coincide with the Cenomanian-Turonian boundary source rocks and top of the Turonian marine shale unit. The shale detachments are inferred to be moderately overpressured. The Late Cenozoic slumping event creates S to WSW and N to ENE dipping normal faults that cross-cut one another. The thrust faults and S to WSW dipping normal faults were interpreted as possible conduits for hydrocarbon migration to the seafloor to form pockmarks. Large submarine canyons were interpreted to have formed by a combination of the two slumping events. This study is the first attempt to constrain the tectonic history of the deepwater Orange Basin through the interpretation of high-resolution 3D seismic data acquired for hydrocarbon exploration. In this study, it is proposed that high-resolution 3D seismics should be recognised as a fundamental geophysical method in studying the tectonic history of the region and to detect hydrocarbons and structures that affect these economic resources.
Keywords: Seismic prospecting; Seismic reflection method; Seismology--Methodology